Kinetics and Mechanism of Ammonium Ion Adsorption Using Natural Zeolite - Mordenite - Halimoon, Normala (2001)
Mordenite, one of the natural zeolites , has the capacity to remove ammonium ion from wastewaters through adsorption phenomenon. This study is a preliminary work of using mordenite to remove ammonium in effluent for tertiary treatment. The feasibility of using mordenite to remove ammonium ion in aqueous solution was carried out using shake flask, stirred tank batch reactor and packed-bed column experiments. The effect of mordenite particle size, ammonium concentration, mordenite concentration, pH, temperature and degree of agitation on the efficiency of adsorption were investigated. The kinetics of ammonium ion sorption was determined using Langmuir and Scatchard sorption isotherm models. The mechanism of ammonium adsorption was investigated using FTIR and electron microscope. In shake flask experiment under equilibrium conditions, the efficiency of ammonium ion removal was optimum at resident time of 6 hours, for granules of 75 µm size, in water containing less than 6 mg/L ammonium ion, in mordenite concentration of 3 g/L, at room temperature, with agitation of 200 rpm and near neutral initial pH (6.5-7.5). Ammonium ion removal of 94% (2.49 mg/g uptake) was achieved when 50 g/L mordenite was used to remove 100 mg/L ammonium concentration under optimum conditions. The sorption isotherm kinetic data of ammonium ion by mordenite fitted well to Langmuir model but did not fit well to Scatchard plot. SEM and FTIR data indicated that ammonium ion was adsorbed on the mordenite particle. When 2 L stirred tank: reactor was used as a contactor, the ammonium uptake capacity ranging from 85-96% was obtained at agitation speed of 200 rpm, concentration of mordenite of 2.67 g/L and 6 mg/L ammonium concentration. Absolute removal of ammonium from solution was achieved when fixed packed-bed column was used as a contactor at low flowrate (2 mL/min) and increased weight of mordenite in the column (48 g), which show less than 5 mg/L ammonium in the effluent before breakthrough was achieved when 100 mg/L ammonium concentration was used . Desorption experiments showed that 37% ammonium recovery in the shake flask and 80-98% in the column contactor. From the study, the result indicated that mordenite has a potential to be promoted as adsorbent that could be used to removed ammonium from solution and can be apply for wastewater treatment.